EFEKTIVITAS PENGGUNAAN ABU SEKAM PADI (Oryza sativa) SEBAGAI ADSORBEN TERHADAP KADAR BESI ( Fe ) PADA PENGOLAHAN AIR BAKU - Yusriani Sapta Dewi; Ai Silmi (FT-USNI, 2023)
Clean water is a basic need for humans. Clean water that meets health requirement and is suitable for use as clean water can be determined by physical, chemical and biological water quality requirement determined by Minister of Health Regulation Number 32 of 2017 concering Environmental Health Quality Standards and Water Health Requirement for Sanitation, Swimming Pools, Solus Per Aqua and public baths which say the level of iron (Fe) in clean water is 1 mg/l. Rice husk is a by-product of the rice milling process which has been a waste that is rarely used and has the potential as an adsorbent for iron (Fe) levels. Ini this study, rice husks were prepared with two treaments without activation and with 30% NaOH activation after baing heated in a furnace at 400oC for 1 hour. The adsorbent was then tasted with groundwater containing high levels of iron (Fe) with an adsorbent weight of 5 grams, where the adsoption process was carried ot with contact time, namely 2 hours and 4 hours. The optimum adsorption process was obtained at contact time of 4 hours and with an activation treatment with average percentage of 70,644%.